Modification of hydrogel for device fabrication - Neo, Glen Say Chew (2019)
Kevlar has long been used as a bulletproof material for military or any defense organization, however it is rather expensive to produce as it involves a complex process of spinning fibers and use of sulfuric acid. This project focuses on exploring hydrogel as a possible alternative for Kevlar in the future. Hydrogel is used for many applications. Ranging from diapers, towels to contact lenses. These are polymers which are not only useful but effective at their uses. The fiber used for the hydrogel is called CNF, also known as Cellulose Nanofiber. In its crystalline form, CNF has interesting mechanical properties in using for material applications. The tensile strength is estimated to be similar to aluminium, at 500MPa and its stiffness is at 140-220GPa which is comparable to Kevlar and higher than glass fiber. Fibers made from cellulose generally have high strength and stiffness. Cellulose is expected to enhance the fiber-fiber bond strength which gives a strong reinforcement on paper materials. This project also uses other compounds and mix with CNF to make hydrogel in hopes to achieve a better tensile strength and stiffness than CNF.